5-(N, N-Hexamethylene) amiloride is a GABA-A ρ1 receptor positive allosteric modulator. Issue 6 (1st November 2016) - Snell, Heather D.; Gonzales, Eric B.
ABSTRACT: Guanidine compounds act as ion channel modulators. In the case of Cys-loop receptors, the guanidine compound amiloride antagonized the heteromeric GABA-A, glycine, and nicotinic acetylcholine receptors. However, amiloride exhibits characteristics consistent with a positive allosteric modulator for the human GABA-A (hGABA-A) ρ1 receptor. Site-directed mutagenesis revealed that the positive allosteric modulation was influenced by the GABA-A ρ1 second transmembrane domain 15′ position, a site implicated in ligand allosteric modulation of Cys-loop receptors. There are a variety of amiloride derivatives that provide opportunities to assess the significance of amiloride functional groups (e.g., the guanidine group, the pyrazine ring, etc.) in the modulation of the GABA-A ρ1 receptor activity. We utilized 3 amiloride derivatives (benzamil, phenamil, and 5-(N, N-Hexamethylene) amiloride) to assess the contribution of these groups toward the potentiation of the GABA-A ρ1 receptor. Benzamil and phenamil failed to potentiate on the wild type GABA-A ρ1 GABA-mediated current while HMA demonstrated efficacy only at the highest concentration studied. The hGABA-A ρ1 (I15'N) mutant receptor activity was potentiated by lower HMA concentrations compared to the wild type receptor. Our findings suggest that an exposed guanidine group on amiloride and amiloride derivatives is critical for modulating the GABA-A ρ1 receptor. The present study provides a conceptual framework for predicting which amiloride derivatives will demonstrate positive allosteric modulation of the GABA-A ρ1 receptor.